The Recantation By The Al-Zaher People And Its Effects in Derivation - علي حاتم الحسن هدى وديع جبار (College of Education for Women, 2019)
nouns , because deriving these names will lead to eternity which is impossible, and restrict the derivation only in agent nouns from their verbs, and the adjective names from their adjectives with the condition of truth in derivation. The derivation of "Allah" names was denied due to a creed thoughts, because saying that "Allah" names is derived will not describe the eternal essence of "Allah", and if it were derived this will make "Allah" is a Compound from his essence and Attributes. The Al-Zaher people had recant the derivation of the agent nouns by preventing the derivation of "Allah" names because it will make "Allah" is a Compound from his essence and Attributes. The Al-Zaher people had recant from forbidding derivation of "Allah" names to allow it in (speaker) to confirm the Words of Allah, while they accept to derive the verb Attributes due to The appearance of these verbs in another places (Human), but the Attributes of "Allah" has been denied from being derived.